2016
DOI: 10.1186/s12876-016-0550-0
|View full text |Cite
|
Sign up to set email alerts
|

The incidence, presentation, outcomes, risk of mortality and economic data of drug-induced liver injury from a national database in Thailand: a population-base study

Abstract: BackgroundToxic liver diseases are mainly caused by drug-induced liver injury (DILI). We assessed incidences and outcomes of DILI including associated factors for mortality.MethodsWe performed a population-based study of hospitalized patients with DILI. Information was retrieved from the Nationwide Hospital Admission Data using ICD-10 code of toxic liver diseases (K71) and additional codes (T36–T65). The associated factors were analyzed with log-rank test, univariate and multiple cox regression analysis.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 17 publications
0
31
1
Order By: Relevance
“…Similar to our study, Devarbhavi et al had reported DILI contributed to 1.4% of all gastrointestinal admissions and 2.5% of hepatobiliary admissions over one year 18 . In a Thailand study; 1.2% of admissions was due to DILI 19 . The results of Meier et al, 2005 were with 1.4% DILI occurrence in hospitalized patients in Switzerland 20 .…”
Section: Discussionmentioning
confidence: 96%
“…Similar to our study, Devarbhavi et al had reported DILI contributed to 1.4% of all gastrointestinal admissions and 2.5% of hepatobiliary admissions over one year 18 . In a Thailand study; 1.2% of admissions was due to DILI 19 . The results of Meier et al, 2005 were with 1.4% DILI occurrence in hospitalized patients in Switzerland 20 .…”
Section: Discussionmentioning
confidence: 96%
“…Estimations of population‐based incidence rates ranged from 13.9 cases per 100 000 inhabitants in France to 19.1 cases per 100 000 inhabitants in Iceland. Rates of DILI are higher in hospitalized patients, ranging from 0.12 to 1.4 per 100 admissions . Although DILI is rare, the consequences could be severe.…”
Section: Introductionmentioning
confidence: 99%
“…This NHSO database is nationwide study, and its coverage of at least of 67.6% of the population of Thailand in 2013 and this database were used and validate in several studies including disease burden of cirrhosis, drug induced liver injury and liver abscess [1214]. Most of ICC patients presented with advanced stages by their clinical findings and complications.…”
Section: Discussionmentioning
confidence: 99%